Neighborhood greenness associated with chronic obstructive pulmonary disease: A nationwide cross-sectional study in China. (November 2020) - Fan, Jing; Guo, Yawei; Cao, Zheng; Cong, Shu; Wang, Ning; Lin, Hualiang; Wang, Chongjian; Bao, Heling; Lv, Xueli; Wang, Baohua; Gao, Yi; Chen, Yahong; et al.
Highlights: Neighborhood greenness is associated with increased prevalence of COPD. The results are consistent across different greenness buffer sizes. Younger adults and urban residents might be the vulnerable subpopulations. Abstract: Differential findings have been reported on the association between neighborhood greenness and chronic obstructive pulmonary disease (COPD). The underlying reasons might be the different types of vegetation and the diagnosis methods used in different studies. In this nationwide cross-sectional study in China, we examined the linkage between neighborhood greenness and COPD prevalence among 66, 752 adults aged 40 years and above. Neighborhood greenness was estimated using the normalized difference vegetation index (NDVI) based on satellite imagery within buffers of 100, 300, 500, 1000, 2000, 3000 and 5000 m of residential community of the participants. COPD was defined according to the 2017 Global Initiative for Chronic Obstructive Lung Disease lung function criteria. A two-level logistic regression model was applied to estimate the associations. Finally, 9134 adults were classified as COPD. We observed significant positive associations between neighborhood greenness and COPD prevalence. The odds ratio for each interquartile range increase in NDVI within 100 m buffer was 1.08 (95% CI: 1.01, 1.15) after adjustment for potential confounders. Consistent associations were observed across all other NDVI buffer sizes. Stratified analyses revealed that younger adults (40–65 years) and urban residents might be the vulnerable subpopulations. Further regional analyses found that residents from the Northeastern and Northern China were more likely to have this association. Our results indicated that neighborhood greenness might be one risk factor of COPD prevalence. Our study have important public health implications for allocating the surrounding green spaces among living areas, especially for those with respiratory illness; however, the findings and the underlying mechanisms warrant further examinations in longitudinal settings.